Foraging habits in a generalist predator: Sex and age influence habitat selection and resource use among bottlenose dolphins ( Tursiops truncatus ) - Sam Rossman; Elizabeth Berens McCabe; Nélio B. Barros; Hasand Gandhi; Peggy H. Ostrom; Craig A. Stricker; Randall S. Wells (Marine Mammal Science, 2015)
This study examines resource use (diet, habitat use, and trophic level) within and among demographic groups (males, females, and juveniles) of bottlenose dolphins ( Tursiops truncatus ). We analyzed the δ 13 C and δ 15 N values of 15 prey species constituting 84% of the species found in stomach contents. We used these data to establish a trophic enrichment factor ( TEF ) to inform dietary analysis using a Bayesian isotope mixing model. We document a TEF of 0‰ and 2.0‰ for δ 13 C and δ 15 N, respectively. The dietary results showed that all demographic groups relied heavily on low trophic level seagrass‐associated prey. Bayesian standard ellipse areas ( SEA b ) were calculated to assess diversity in resource use. The SEA b of females was nearly four times larger than that of males indicating varied resource use, likely a consequence of small home ranges and habitat specialization. Juveniles possessed an intermediate SEA b , generally feeding at a lower trophic level compared to females, potentially an effect of natal philopatry and immature foraging skills. The small SEA b of males reflects a high degree of specialization on seagrass associated prey. Patterns in resource use by the demographic groups are likely linked to differences in the relative importance of social and ecological factors.